Charmian Clift, Brenda Chamberlain, and the dichotomous freedom of Hydra - Genoni, Paul (Association for the Study of Australian Literature, 2019)
This essay draws a comparison between two published memoirs of participants, both of them women writers, in the Hydra expatriate community of the 1950s and ’60s: Australian Charmian Clift’s Peel Me a Lotus, and Welsh artist and writer Brenda Chamberlain’s A Rope of Vines. As memoirs of female experience on Hydra the two texts have elements in common, but the contrasts are also stark. Whereas Clift focused on family life, the bucolic harbourside agora and the boisterous life of the taverns and kafenia, Chamberlain represented herself as being alone and declared, ‘the port and the people on it do not interest me.’ For Chamberlain, the dockside was a place of ‘unreal glamour’ that deadened her creative spirit as surely as it deflected Hydra’s international visitors from understanding the true nature of the island they superficially embraced.